A anáfora encapsulada como objeto de discurso na construção do sentido no gênero textual notícia - Welter, Graciele Hilda (2009)
This dissertation presents a textual anaphora study as an object of discourse, produced by the discursive activity, which contributed to the construction of meanings in the texts. In the light of the textual linguistic studies, it is observed the occurrence of encapsulating anaphora in seven Zero Hora newspaper articles, reported between January and May 2009. The theoretical foundation presents as main authors Ingedore Villaça Koch, Luiz Antônio Marcuschi, Denis Apothéloz, Lorenza Mondada, Daniele Dubois and Monica Magalhães Cavalcante. The survey performed shows that the anaphora, as an object of discourse, is an important referral strategy, of organization, and textual understanding that is able to guide the construction and reconstruction of the meanings of a text. After the anaphora survey (formed by nominal synthetized expression) present in each article, we found its accomplishment in the corpus under study, and we proceed to its analysis, acording to previously established criteria. We note the relevance of the studied phenomenon to the organization of the text and for conveying the meaning to be constructed by the reader